Pembelajaran Matematika Anak Usia Dini Melalui Media Dadu dan Pengaruhnya ditinjau dari Perkembangan Kognitif - Qudsi Amin; Erna Wijayanti; Irmaidah Irmaidah (Program Studi Pendidikan Matematika IKIP PGRI Jember, 2019)
Learning mathematics for early childhood requires ways and media that are suitable for children's development. Mathematics is a scientific discipline that covers almost all levels of education including early childhood education. The characteristic of early childhood learning is learning while playing as embodied in its curriculum at the level of the National Education System. Media dice games can be used in mathematics learning numerical recognition material that is directly related to aspects of children's cognitive development. This study examines the effect of dice media on cognitive development in the mathematics learning of early childhood education number recognition material. This type of research is quantitative causal with statistical tests used including normality test and homogeneity test and hypothesis testing using T test (T-test) or partial test using SPSS version 22 program. The conclusion of this study is that there are influences of media dice game on cognitive aspects learning material for number recognition in learning early childhood mathematics in the 2018/2019 academic year.